Predisposing factors associated with stillbirth in Tanzania. Issue 1 (July 2015) - Kidanto, Hussein; Msemo, Georgina; Mmbando, Donan; Rusibamayila, Neema; Ersdal, Hege; Perlman, Jeffrey
Abstract: Objective: To determine whether specific medical conditions and/or fetal compromise during labor are associated with fresh stillbirth (FSB), and whether absent fetal heart rate (FHR) before delivery can increase risk of FSB. Methods: An observational cohort study was conducted at three university referral hospitals in Tanzania between January and September 2013. Maternal, labor, and neonatal characteristics were recorded for all deliveries. FSB was defined as an Apgar score of 0 at 1 and 5 minutes, with intact skin and suspected death during labor or delivery. Results: Among 15 305 deliveries, there were 499 stillbirths (243 FSBs and 256 macerated stillbirths). Stillbirth was significantly more likely than a live birth after maternal transfer (odds ratio [OR] 3.27; 95% confidence interval [CI] 2.73–3.92; P  < 0.001) and when FHR was absent (OR 996.29; 95% CI 632.19–1570.09; P  < 0.001). Risk of stillbirth increased with uterine rupture (OR 138.62; 95% CI 60.73–316.44), placental abruption (OR 40.96; 95% CI 28.97–57.91), cord prolapse (OR 13.49; 95% CI 6.97–26.11), and prematurity (OR 6.87; 95% CI 4.71–10.03; P  < 0.001 for all). Conclusion: In low-resource settings, FSB may be prevented by using a combined strategy of clinical risk identification, early detection of abnormal FHR, and expedited delivery.